Bearing Capacity and Deformability of Three-Component Steel Reinforced Concrete Constructions Made of Lightweight Concrete - Semko, Oleksandr; Hasenko, Anton; Mahas, Nataliia; Sirobaba, Vitalij (International Journal of Engineering and Technology, 2018)
The article contains the study of strength and deformability of three-component steel-reinforced concrete structures made of a thin-walled steel shell, light concrete and rigid reinforcement in the form of a light steel thin-walled profile. The results of calculation, simulation and experimental researches of more than 40 steel-concrete elements are presented. The diagrams of the work of these constructions are compared with the comparison of experimental data and numerical modeling, which confirm the correctness of the introduction of the calculation model into the software complex, where special attention was paid to the boundary conditions of the work of the structure. The model with the indication of the concentration of internal stresses and the nature of the deformation of the structure in general, which fully corresponded to the experimental research, was analyzed.  An adapted calculation algorithm for three-component steel-concrete constructions is presented, where the coefficients of working conditions for each of the constituent constructions are indicated. The relationship between relative flexibility and the lowering coefficient of operation of a thin-walled cylindrical steel shell is shown. Appropriate conclusions are formulated.
Keywords: deformability; flexibility; lightweight concrete; steel-reinforced concrete constructions; strength; thin-walled steel shell/